Combustion and Thermal Properties of Flame Retardant Polyurethane Foam With Ammonium Polyphosphate Synergized by Phosphomolybdic Acid - Xu, Zhirong; Xu, Zihui; Tao, Ran; Mao, Liangchen; Zhan, Jing; Xiao, Junfeng; Yu, Tao (Frontiers in Materials, 2022)
Phosphomolybdic acid (PMA) as a synergist was added into polyurethane (PU) rigid foam with ammonium polyphosphate (APP) to improve its flame retardancy and thermal stability. The combustion performance of PU was studied by limiting oxygen index (LOI), UL-94 and cone calorimeter. The thermal degradation behavior of PU was determined by thermogravimetric analysis (TG) and thermogravimetric infrared spectroscopy (TG-IR). Experimental results showed that the introduction of PMA could further improve the flame retardant performance of PU/APP composites and significantly increase the amount of carbon residue at high temperature. Adding 3wt% PMA to PU containing 12wt% APP could make the foam pass UL-94 V-0, increase the carbon residue at 800℃ by 69.16% in air atmosphere, and decrease the THR by 24.62% compared to those of PU/15APP. TG-IR results showed that the presence of PMA reduced the production of small molecule gas phase products. The results suggest that PMA and APP have good synergistic flame retardancy on PU and can reduce its fire risk.